Research note: Ski touring on groomed slopes and the COVID-19 pandemic as a potential trigger for motivational changes. (March 2023) - Schlemmer, Philipp; Schnitzer, Martin
Abstract: Ski touring on groomed slopes is a relatively new outdoor sport that has steadily been gaining interest. So far, little scientific attention has been given to this outdoor activity. Thus, few questions have been asked about the motivation for practising this sport, and even fewer about whether the current COVID-19 pandemic has had an impact on the frequency of and motivation for ski touring. For this reason, we conducted a large-scale study (n = 6802) in the Austrian Alps. Results revealed that the COVID-19 pandemic has not changed the motive structure for ski touring; however, the findings showed that many people have even started to practice this sport. This research note contributes to the existing knowledge by (a) documenting ski tourers' motives using a large sample, (b) giving insights into the effects of the COVID-19 pandemic on this specific outdoor sport, and (c) showing COVID-19-related impacts on practicing ski touring. Management implications: No changes in motivational reasons for ski touring due to COVID-19 pandemic. Trend towards outdoor sports, especially ski tours on groomed slopes in the alpine region of central Europe. Amplification of the trend due to the pandemic and the associated restrictions. As an outdoor sport, ski touring on groomed slopes offers versatile added value for ski tourers, but also huge potential for ropeway operators. This soft slope tourism can also show alternatives to temporary ropeway closures in times of the COVID-19 pandemic and could also promote tourism (especially day tourism) in small circles at the regional level. The increase in beginners naturally raises the question of whether this group needs special offers or how to deal with beginners on the slopes. On the other hand, this also raises the question of how to deal with the increase in ski slope users in general.